Metastasis to Paranasal Sinuses from Carcinoma of Prostate: Report of a Case and Review of the Literature - Elio Bittar Barbosa; Evaldo César Macau Furtado Ferreira; Fernanda Viviane Mariano; Albina Messias de Almeida Milani Altemani; Emerson Taro Inoue Sakuma; Eulalia Sakano (Case Reports in Otolaryngology)
Metastasis from distant primary tumors is extremely rare in the paranasal sinuses with few hundred cases in the literature. Metastatic carcinoma of the prostate is even rarer, despite being one of the most common tumors, with only 24 cases published. In this article, we report a case of a 58-year-old male presenting with epistaxis and nasal obstruction as initial symptoms of a metastatic prostate carcinoma in the ethmoid cells and maxillary sinus.